2011
DOI: 10.1161/circresaha.110.237206
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Engineered Human Myocardium With Mechanical Loading and Vascular Coculture

Abstract: Rationale The developing heart requires both mechanical load and vascularization to reach its proper size, yet the regulation of human heart growth by these processes is poorly understood. Objective We seek to elucidate the responses of immature human myocardium to mechanical load and vascularization using tissue engineering approaches. Methods and Results Using human embryonic stem cell and human induced pluripotent stem cell-derived cardiomyocytes in a three dimensional collagen matrix, we show that unia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
622
3
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 600 publications
(640 citation statements)
references
References 73 publications
14
622
3
1
Order By: Relevance
“…82 In another study, it was demonstrated that uniaxial mechanical loading promoted the cardiomyocyte differentiation of human ESCs within 3D collagen hydrogels. 83 It was found that the application of mechanical stimulation enhanced cardiomyocyte alignment, hypertrophy, proliferation as well as the formation of sarcomeric bands. To further improve the function of engineered cardiac tissue construct, ECs and stromal cells were co-cultured with ESC-derived cardiomyocytes to form a tissue construct containing highly vascularized networks.…”
Section: Directing Stem Cell Differentiation Into Cardiac Lineagementioning
confidence: 99%
“…82 In another study, it was demonstrated that uniaxial mechanical loading promoted the cardiomyocyte differentiation of human ESCs within 3D collagen hydrogels. 83 It was found that the application of mechanical stimulation enhanced cardiomyocyte alignment, hypertrophy, proliferation as well as the formation of sarcomeric bands. To further improve the function of engineered cardiac tissue construct, ECs and stromal cells were co-cultured with ESC-derived cardiomyocytes to form a tissue construct containing highly vascularized networks.…”
Section: Directing Stem Cell Differentiation Into Cardiac Lineagementioning
confidence: 99%
“…A variety of stem cell sources (embryonic stem cells, induced pluripotent stem cells, cardiac stem cells, adipose stem cells, etc.) have also been used to generate immature CM using a variety of CM lineage specification and selection protocols [10][11][12][13][14]. Not surprisingly, stem cell populations can be rapidly expanded in vitro along with the induction of cardiac lineages; however, their functional maturation remains a major technical challenge [15][16][17].…”
Section: Immature Cells For Engineered Cardiac Tissuesmentioning
confidence: 99%
“…Because human cells are required for clinical translation, the optimization of protocols that can generate large quantities of functional human CM is a high priority for cardiac repair strategies. Further, there may be advantages to generating ECTs that contain both cardiac and vascular lineage cells to accelerate angiogenesis and vascular perfusion of implanted ECTs [11][12][13]. …”
Section: Immature Cells For Engineered Cardiac Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of cells into a hydrogel is one of the oldest ideas in tissue engineering, which was introduced 35 years ago [93] and was applied to generate the first engineered cardiac tissues [94]. The most commonly used hydrogels are based on collagen I [87], Matrigel [95], fibrin [88, 89••, 96], and mixtures thereof. The principle is always similar: cells are mixed with the hydrogel and filled into a casting mold that determines the shape of the engineered tissue.…”
Section: Approaches For the Use Of Pluripotent Stem Cell Products In mentioning
confidence: 99%